Dieckol, a Major Marine Polyphenol, Enhances Non-Rapid Eye Movement Sleep in Mice via the GABAA-Benzodiazepine Receptor - Yoon, Minseok; Kim, Jin-Soo; Seo, Sangwoo; Lee, Kiwon; Um, Min Young; Lee, Jaekwang; Jung, Jonghoon; Cho, Suengmok (Frontiers in Pharmacology, 2020)
In our previous study, we demonstrated that marine polyphenols, phlorotannins, promote sleep in mice via the GABAA-benzodiazepine (BZD) receptor. Among the constituents of phlorotannin, dieckol is a major marine polyphenol from the brown alga Ecklonia cava. Although phlorotannins are known to exert hypnotic effects, the sleep-enhancing effect of dieckol has not yet been determined. We evaluated the effect of dieckol on sleep-wake profiles in mice by analyzing electroencephalograms (EEG) and electromyograms. Flumazenil, a GABAA-BZD antagonist, was used to investigate the molecular mechanism underlying the effects of dieckol on sleep. The polygraphic recordings and corresponding hypnograms revealed that dieckol accelerated the initiation of non-rapid eye movement sleep (NREMS), as it reduced sleep latency and increased NREMS duration. According to the time-course change, dieckol shows sleep-enhancing effects by increasing the amount of NREMS and decreasing the wakefulness during the same hours. Additionally, sleep quality was evaluated by analyzing the EEG power density and we found that dieckol does not affect sleep intensity, whereas zolpidem decreased it. Finally, we treated mice with zolpidem or dieckol in combination with flumazenil and found that flumazenil inhibits the sleep-enhancing effect of dieckol and zolpidem, which indicates that dieckol exerts sleep-enhancing effects by activating the GABAA-BZD receptor, as zolpidem does. These results imply that dieckol can be used as a promising herbal sleep aid with minimal the side effects, unlike existing hypnotics.